Reasons for Flouting Maxim in Talk Show - Irawan, A A Ayu Cindy Karina Ivana; Beratha, Ni Luh Sutjiati; Sukarini, Ni Wayan (Humanis, 2021)
This study is entitled Reasons for Flouting Maxim in Talk Show. The aim is to analyze the types of flouting maxim used by the participants in the talk show through their utterances based on theory of Conversational Maxim proposed by Grice and supporting theory Context of Situation by Halliday & Hasan to see how the maxim is flouted. The data was taken from one of the famous American talk shows which contains various topics of talk and the implementation of the conversational maxim, it is The Ellen Show. The data was collected by using observation method. Descriptive qualitative method was used as a method and technique of analyzing data. The data was presented in a form of words and sentences. The results show that all types of maxim are flouted in the talk show. The most flouted maxim found in conversation is maxim of quantity because the participants deliver more information than it is required even though that experience is based on their experiences.